Talent development versus talent management: unblurring the lines for workforce and organizational performance - Osolase, Ehikioya H.; Mohd Rasdi, Roziah; Mansor, Zuraina D. (SAGE Publications, 2023)
In reference to workforce development for organizational performance, the blurry lines between talent development and talent management have resulted to several HRD scholars interchangeably using talent management in replacement of talent development. However, talent development as an HRD function supersedes talent management. Therefore, to demarcate the existing lines which exists between both, it is important that HRD practitioners develop the required awareness. Talent development is a necessity for efficient management of people. To bring about a fundamental change on the need to clearly differentiate between talent development and talent management, the expertise of HRD practitioners in collaboration with industry professionals, is required to develop new knowledge and models for workforce and organizational performance. Scholars and practitioners of human resource development and other fields within the management discipline, in addition to managers and the workforce across all sectors in various industries.